2020
DOI: 10.14715/cmb/2020.66.7.27
|View full text |Cite
|
Sign up to set email alerts
|

miR-196a targeting LRIG3 promotes the proliferation and migration of cervical cancer cells

Abstract: In recent years, studies have found that miR-RNA plays a role in cell proliferation, differentiation, apoptosis and metabolism. Among them, miR-196a is closely related to cervical cancer. Therefore, this experiment investigates the effect of mir-196a expression on cervical cancer cells and related mechanisms. The expression level of miR-196a in the cervical cancer cell line was assayed with the RT-PCR method, and liposome transfection was used to investigate its up-regulation or down-regulation in cervical can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…miR-196a plays an important regulatory role in organisms and has been found to be upregulated in a variety of malignant tumors. miR-196a affects the proliferation, invasion, and apoptosis of tumor cells and is expected to become a new molecular marker or target for tumor diagnosis, treatment, and prognosis, indicating its potential in clinical applications [ 38 , 39 , 40 , 41 ]. Several studies have also reported that miR-196b is highly expressed in multiple malignant tumors and has the characteristics of an oncogene to promote tumorigenesis [ 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-196a plays an important regulatory role in organisms and has been found to be upregulated in a variety of malignant tumors. miR-196a affects the proliferation, invasion, and apoptosis of tumor cells and is expected to become a new molecular marker or target for tumor diagnosis, treatment, and prognosis, indicating its potential in clinical applications [ 38 , 39 , 40 , 41 ]. Several studies have also reported that miR-196b is highly expressed in multiple malignant tumors and has the characteristics of an oncogene to promote tumorigenesis [ 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Lrig3 expression is directly modulated by miRNA-196a, a microRNA that is upregulated in gastric, colon, breast and pancreatic cancer and promotes tumorigenesis. In cervical cancer cells, miRNA-196a targets Lrig3 (19) and improves cell viability. Lrig3 is also regulated at the post-transcriptional level, as there are reports of a circular form of Lrig3 (circRNA Lrig3 ) that is highly expressed in human hepatocellular carcinoma (HCC).…”
Section: Discussionmentioning
confidence: 99%
“…CC is the most common in Sub-Saharan Africa, accounting for more than 90% of all cases and 70% of cervical cancers occur in developing countries [6]. HIV (Human Immunodeficiency Virus) affected women must be aware of this cancer because these patients are significantly vulnerable to getting infected by cancer [7].…”
Section: Introductionmentioning
confidence: 99%